2022
DOI: 10.2147/jir.s338421
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inflammatory-Nutritional Prognostic Scoring System for Patients with Early-Stage Breast Cancer

Abstract: Purpose We attempted to explore the prognostic value of baseline inflammatory and nutritional biomarkers at diagnosis in patients with early-stage breast cancer and develop a novel scoring system, the inflammatory-nutritional prognostic score (INPS). Patients and Methods We collected clinicopathological and baseline laboratory data of 1259 patients with early-stage breast cancer between December 2010 and November 2012 from Sun Yat-sen University Cancer Center. Eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…They also conducted a nomogram based on INPS for survival prediction in resected stage III gastric cancer with adjuvant chemotherapy. Hua et al ( 34 ) also validated the prognostic value of INPS by LASSO regression analysis in 1,259 patients with early stage breast cancer. In another study including 334 patients with limited-stage small cell lung cancer, the authors also indicated that several hematological nutritional and inflammatory indexes were associated with OS ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also conducted a nomogram based on INPS for survival prediction in resected stage III gastric cancer with adjuvant chemotherapy. Hua et al ( 34 ) also validated the prognostic value of INPS by LASSO regression analysis in 1,259 patients with early stage breast cancer. In another study including 334 patients with limited-stage small cell lung cancer, the authors also indicated that several hematological nutritional and inflammatory indexes were associated with OS ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nomogram, as a prognostic statistical model, can not only visually display the relevant indicators affecting the outcome in Cox PH regression analyses but also predict the survival probability through a simple graphical representation, which makes the prediction more simple and convenient ( 44 ). Wang et al ( 33 ) and Hua et al ( 34 ) both established a nomogram based on INPS to predict prognosis. They also revealed that the INPS-based prognostic nomogram showed a good prognostic stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that preoperative INPS is an independent predictor of outcomes for stage III GC patients [31]. Hua et al demonstrated that patients with high INPS had significantly worse survival than those with low INPS [32]. In that research, the authors chose the LASSO regression model to establish the INPS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the diagnostic efficiency of the dysregulated metabolites was evaluated. As a good method in machine learning, LASSO regression has been widely used in cancer marker studies (Hua et al, 2022;Koplewitz et al, 2022). In this study, with LASSO regression analysis, we constructed two risk models with the seven key metabolites for NIHL status predication.…”
Section: Central Carbon Metabolismmentioning
confidence: 99%